An Evaluation of the Teacher Service Training Program at Islamic Boarding School: A Study of the Kirkpatrick Model - Mawaddah, Nurul; Rasyid, Muhammad Nur Akbar; Mania, Sitti (ETDC: Indonesian Journal of Research and Educational Review, 2025)
There is an urgent need to enhance the professionalism of teachers, especially in Islamic boarding schools, to effectively tackle the challenges of modern education without compromising traditional Islamic values. Although teacher training evaluations have been widely conducted, gaps remain in the evaluation of the provision for new graduates before serving. The goal of this study is to assess the effectiveness of the teacher service training program at Islamic Boarding School using the Kirkpatrick evaluation model approach. This study uses a qualitative approach with an evaluation type of Kirkpatrick evaluation model that refers to two initial levels: reaction and learning. This research was conducted at the As'adiyah Sengkang Islamic Boarding School. Data were obtained through interviews, observations, documentation, and FGDs with participants, facilitators, and program managers. The evaluation results show that at the reaction level, participants gave very positive responses to the relevance of the material, teaching methods, the quality of the facilitators, and the learning environment. Meanwhile, at the learning level, there was a significant increase in participants' cognitive, affective, and psychomotor competencies, including the ability to integrate As'adiyah values into learning practices. These findings indicate that the training program has succeeded in forming prospective teachers who are not only technically skilled but also have character. Recommendations based on the evaluation results include the need for continued development, improved technological facilities, and further evaluation at the behavioral and outcome levels to measure long-term impact.